Model of the post-war development of the agro-industrial complex of Ukraine: Prognostic and financial concept - Novikov, Oleksandr; Pasichnyk, Yurii (Вісник аграрної науки Причорномор'я, 2022)
The article is devoted to the formation of the post-war model of development of the agro-industrial complex of Ukraine. The topicality of the topic consists in determining the means of restoration and further development of the agro-industrial complex with appropriate justification of the proposed model, which will contribute to solving the problems of providing food to Ukrainian and foreign consumers. Considering the specifics of the research, the main method was chosen to be systematic, which ensures the complexity of the research. Along with it, the methods of comparisons, formalization, and economic analysis were used, which make it possible to supplement and expand the scope of the research to obtain a scientifically based result. The purpose of the article is to substantiate the prognosticfinancial concept of the restoration model of the agricultural industry of Ukraine in the post-war period. The article analyzes the pre-war state of the agro-industrial complex according to the main criteria and reveals the reasons for inefficient use of its potential. A comparison of the efficiency of agricultural production based on the indicator of added value was made in Ukraine with such countries as Poland, Brazil, Germany, France, where Ukraine was found to be significantly behind. It is also emphasized that a small share of Ukrainian agricultural raw materials is sent to industrial processing, which significantly reduces the amount of added value. Taking into account the importance of the influence of external environmental factors on the functioning of the agro-industrial potential at the present time, an analytical justification of this influence in cost calculation is provided. Using the system method, an algorithm for the development of the specified model was proposed, the hierarchy and structure of the development of this complex were substantiated, six principles were determined, scientific approaches were developed for the formation of a prognostic model of the post-war development of the specified complex in experimental and working versions, and the conditions for its implementation were highlighted. The scientific novelty of the article lies in the development of theoretical provisions, which together made it possible to propose a predictive model of the development of the agro-industrial complex of Ukraine in the post-war period, which will contribute to the restoration and further development of the entire specified complex with sustainable provision of national food security